Doença renal crônica : a evolução da patologia associada à citocinas e fatores bioquímicos - Alves, Josilene Dália (2016)
Chronic kidney disease (CKD) is currently considered a problem of global public health. In the later stages, the CKDis mainly characterized by dysfunction of the immune system and alterations in lipid metabolism and minerals. These complications contribute directly to higher rates of morbidity and mortality of these patients. This study aims to investigate possible associations between cytokines and potassium, calcium, phosphorus, total cholesterol and High Density Lipoproteins (HDL), cholesterol in patients with advanced stages of CKD. Serum measurements of total and HDL cholesterol, potassium, calcium, phosphorous, as well as the estimated GFR (glomerular filtration rate) were performed. Quantification of cytokines was performed by cytometry. Statistical differences were evaluated by ANOVA or Kruskal- Wallis test, when indicated. Correlations were analyzed using the Pearson or Spearman test, when apropriated. For this study were considered significant p values <0.05. The study included 92 participants between control subjects and patients with CKD from stages 3, 4 and 5. The results of this study show that serum concentrations of potassium, phosphorus, total cholesterol and HDL cholesterol, as well as IL-6, INF-γ and IL-17A expression are altered in patients with CKD in advanced stages, when compared to the control group, and that these changes tend to get worse as CKD progresses. As IL-6, INF-γ andIL-17A levels increase, so does the serum potassium, phosphorus and total cholesterol, while HDL cholesterol and GFR decline. Besides, potential biomarkers it is possible that these cytokines may become targets for novel immunomodulatory therapies. Our results provide new evidence that CKD patients must be carefully monitored, intendingto reduce their risk for cardiovascular disease, as well as to retard the progression of CKD.